2016
DOI: 10.1098/rsob.160185
|View full text |Cite
|
Sign up to set email alerts
|

The distinct fate of smooth and roughMycobacterium abscessusvariants inside macrophages

Abstract: Mycobacterium abscessus is a pathogenic, rapidly growing mycobacterium responsible for pulmonary and cutaneous infections in immunocompetent patients and in patients with Mendelian disorders, such as cystic fibrosis (CF). Mycobacterium abscessus is known to transition from a smooth (S) morphotype with cell surface-associated glycopeptidolipids (GPL) to a rough (R) morphotype lacking GPL. Herein, we show that M. abscessus S and R variants are able to grow inside macrophages and are present in morphologically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
207
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(217 citation statements)
references
References 79 publications
(153 reference statements)
10
207
0
Order By: Relevance
“…However, there is not much information on the machanisms by which R and S types induce distinct autophagosome formation. Recently, it was demonstrated that the R type induces more autophagy than the S variant, as evidenced by the increased percentage of LC3 formation in infected cells (80). This was in accordance with the study conducted in our lab using the R type clinical isolate, UC22…”
Section: Cellular and Molecular Mechanisms Of Autophagysupporting
confidence: 79%
See 1 more Smart Citation
“…However, there is not much information on the machanisms by which R and S types induce distinct autophagosome formation. Recently, it was demonstrated that the R type induces more autophagy than the S variant, as evidenced by the increased percentage of LC3 formation in infected cells (80). This was in accordance with the study conducted in our lab using the R type clinical isolate, UC22…”
Section: Cellular and Molecular Mechanisms Of Autophagysupporting
confidence: 79%
“…Thus, cording has a crucial role in the pathophysiology of M. abscessus infection as it is a mechanism of immune evasion. The intraphagosomal R and S strains display distinct morphology as the S strain exhibits a thick outermost electron transluscent zone (ETZ) which is apposed to the phagosome membrane all around while the R form produces a very thin ETZ (80).…”
Section: Cellular and Molecular Mechanisms Of Autophagymentioning
confidence: 99%
“…In one study, azithromycin appeared to impair autophagic and phagosomal degradation resulting in decreased mycobacterial clearance (including M. abscessus ) by preventing lysosomal acidification and intracellular killing [184]. The smooth morphotype of M. abscessus was also recently shown to restrict intraphagosomal acidification resulting in reduced apoptosis and autophagy [185]. However, a detailed understanding of autophagy and/or inflammasome pathways as drivers of intracellular persistence and pathogenesis in NTM is still undefined and crosstalk between the two pathways is unknown.…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%
“…Indeed, infection of classical immunocompetent mouse models leads to transient colonization, thus impeding their use as a valuable animal models to study chronic disease and the in vivo therapeutic efficacy of drugs (Bernut et al, 2014b). However, in the past few years the development of multiple cellular, non-mammalian and mammalian models have helped to study the chronology and the pathology of Mabs infection (Byrd and Lyons, 1999; Howard et al, 2006; Ordway et al, 2008; Oh et al, 2013; Bernut et al, 2014a; Bakala N'Goma et al, 2015; Roux et al, 2016). Among these new model systems, a few have been validated for their suitability for in vivo drug efficacy studies against Mabs (Ordway et al, 2008; Lerat et al, 2014; Oh et al, 2014; Bernut et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…A major hallmark of Mabs R is its high propensity to aggregate, leading to the formation of phagocytic cups and the presence of social phagosomes containing usually more than one bacillus. These phagocytic cups and bacterial laden phagosomes are associated with increased cell mortality, evoking a typical trait of RGM (Brambilla et al, 2016; Roux et al, 2016). In contrast, loner phagosomes containing one bacilli are usually found within macrophages infected with the S form (Figure 1).…”
Section: Introductionmentioning
confidence: 99%